Integrating metabolomics for precision nutrition in poultry: optimizing growth, feed efficiency, and health - Abd El-Hack, Mohamed E.; Allam, Ahmed A.; Aldhalmi, Ahmed K.; Kamal, Mahmoud; Arif, Muhammad; Alawam, Abdullah S.; Rudayni, Hassan A.; Taha, Ayman E.; Swelum, Ayman A.; Elolimy, Ahmed A.; Madkour, Mahmoud; Ashour, Elwy A. (Frontiers in Veterinary Science, 2025)
Nutrition is an important factor in poultry production. This review highlights how precision nutrition improves poultry performance through metabolomics, which is a multidisciplinary approach that integrates traditional nutrition with other fields, including biology, immunology, molecular biology, genetics, computer sciences, chemistry, biochemistry, mathematics, engineering, and technology sciences. For measuring the results of the body’s biochemical activities and figuring out Living systems’ dynamic, multi-parametric metabolic response to pathological stimuli, metabolomics can be a very useful instrument. Numerous metabolomics techniques exist, including emerging capillary electrophoresis (CE), gas chromatography mass spectrometry (GC–MS), nuclear magnetic resonance spectroscopy (NMR), liquid chromatography mass spectrometry (LC–MS), inductively coupled plasma mass spectrometry (ICP-MS), and some targeted HPLC-based assays. Metabolomics can help in understanding the metabolism of diets (protein, carbohydrate, and fat) and the pathways of precise nutrition. Metabolomics can revolutionize poultry nutrition strategies, optimizing health, growth performance, and metabolic efficiency by decoding biochemical interactions between diet, metabolism, and physiology. This review aims to highlight methodologies for integrating metabolomic data into precision feeding systems, ultimately enhancing sustainability, reducing production costs, and improving poultry welfare.